PERANCANGAN E-MODULE PERAKITAN DAN INSTALASI PERSONAL KOMPUTER SEBAGAI MEDIA PEMBELAJARAN SISWA SMK - Lidya Rahmi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The research discusses about the design of electronic module assembly and installating computer. The module was designed for assembling and installating computer content displayed in digital way, so this modul is very flexible and easy to be used. The content was displayed by video to make it easier to understand by the learners. The method used consists of several phases; analysis, design, coding and testing. The design used UML process and then was developed by Kvisoft Flip book maker. The result of this research shows how the assembly and installation module was easier to be used for the teacher and the students.